2020
DOI: 10.1186/s40163-020-00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Somehow I always end up alone: COVID-19, social isolation and crime in Queensland, Australia

Abstract: The COVID-19 pandemic has dramatically affected social life. In efforts to reduce the spread of the virus, countries around the world implemented social restrictions, including social distancing, working from home, and the shuttering of numerous businesses. These social restrictions have also affected crime rates. In this study, we investigate the impact of the COVID-19 pandemic on the frequency of offending (crimes include property, violent, mischief, and miscellaneous) in Queensland, Australia. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 48 publications
2
74
0
1
Order By: Relevance
“…These contributions have largely featured case study sites in the United States, including San Francisco and Oakland (Shayegh and Malpede 2020 ), Los Angeles (Campedelli et al 2020 ; Mohler et al 2020 ), Detroit (Felson et al 2020 ), Indianapolis (Mohler et al 2020 ), Dallas (Piquero et al 2020 ) and Chicago (Bullinger et al 2020 ), some examining multiple cities (Ashby 2020a , b ) and nationwide (Hawdon and Dearden 2020 ). Studies have also been conducted in the United Kingdom (Buil-Gil et al 2020b ; Halford et al 2020 ; Kirchmaier and Villa-Llera 2020 ; Office for National Statistics 2020 ), Australia (Andresen and Hodgkinson 2020 ; Payne and Morgan 2020a , b ), Sweden (Gerell et al 2020 ) and Canada (Hodgkinson and Andresen 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These contributions have largely featured case study sites in the United States, including San Francisco and Oakland (Shayegh and Malpede 2020 ), Los Angeles (Campedelli et al 2020 ; Mohler et al 2020 ), Detroit (Felson et al 2020 ), Indianapolis (Mohler et al 2020 ), Dallas (Piquero et al 2020 ) and Chicago (Bullinger et al 2020 ), some examining multiple cities (Ashby 2020a , b ) and nationwide (Hawdon and Dearden 2020 ). Studies have also been conducted in the United Kingdom (Buil-Gil et al 2020b ; Halford et al 2020 ; Kirchmaier and Villa-Llera 2020 ; Office for National Statistics 2020 ), Australia (Andresen and Hodgkinson 2020 ; Payne and Morgan 2020a , b ), Sweden (Gerell et al 2020 ) and Canada (Hodgkinson and Andresen 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The compulsive nature of drug dependency, coupled with the socioeconomic vulnerability of drug user communities, likely means that drug markets remained active despite the government's order to stay-at-home (see Eligh, 2020;Hamilton and Stevens, 2020;Namli, 2021;Winstock et al, 2020) and this activity was likely more visible to law enforcement. These competing hypotheses have been developed mostly in response to the evidence of aggregate data showing state-wide or city-wide changes in drug offence arrest rates (see Andresen and Hodgkinson, 2020;Langfield et al, 2021). Few studies have drilled down into the geospatial data to examine the spatiotemporal patterns and their implications for understanding both drug markets and policing during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…According to RAT, it is possible that drug market activity may have increased as guardianship temporarily declined. Conversely, others have elsewhere indicated that both property and violent offending have decreased in the absence of suitable targets (Abrams, 2020;Andresen & Hodgkinson, 2020;Ashby, 2020;Campedelli et al, 2020;Davey, 2020;Freeman, 2020;Gerrel et al, 2020;Mohler et al, 2020;Payne et al, 2020Shepherd, 2020). Paradoxically, the suitable target for a property offender is also the capable guardian of a local drug market so it makes sense that drug detections could increase while property and other offences decline.…”
Section: Lessons From Before the Pandemicmentioning
confidence: 99%